EFEKTIVITAS PELAYANAN PEMBERIAN IZIN MENDIRIKAN BANGUNAN (IMB) DI KABUPATEN SLEMAN - , FANNI FADHILASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This internship report is aimed to discuss aboutthe effectiveness of government service to the citizen in building established license (IMB) at the district of Sleman office, where that still have the problems from the government itself. The peoples are unsatisfiedtoward the services. The effect of this policy making less awareness of the people. The practices will be the author as a professional in legal science. The author must becreative, competent, and could help to solve the problems ofservice for giving building established license(IMB) at the district of Sleman. Therefore, It can be increase up the awareness of the society toward that. The government services who has given by the bureaucracy was good enough but still have the problem of the application for asking of the service for giving building established license (IMB). One of the problem was the citizen ununderstand the procedure of the service for giving license (IMB). Why it happened because the implementation from the government about given the imformation, knowledge, and advocacy about the procedure and the service for giving license was ineffective, it impact there were so many complain from the citizens. Based on the local rule (PERDA) about that needed only 2,5 months. However the fact was not like that.